Identifying the Multi-Role Dynamics of High-quality Scientific and Technological Human Resources in Contemporary Universities and Policy Recommendations for Project-Based Training Models - Thanh Tuan, Nguyen (VNU Journal of Science: Policy and Management Studies, 2025)
In the context of accelerating innovation, digital transformation, and global integration, high-quality scientific and technological human resources in universities are increasingly taking on diverse roles — ranging from teaching and research to knowledge transfer, industry–community engagement, policy advising, and social innovation entrepreneurship. This trend toward multi-role engagement introduces new demands for the design of training strategies and human resource development models. This paper analyzes the distinctive manifestations of multi-role practices in the current academic landscape, identifies key challenges related to individual capacity, institutional environments, and academic governance, and proposes project-based training through scientific and technological initiatives as an effective approach to comprehensive human resource development. Such a model bridges theoretical knowledge with practical applications and fosters flexible learning environments where learners can develop interdisciplinary competencies, systems thinking, and high adaptability. Based on these insights, the paper offers a set of strategic recommendations to reorient training philosophies, cultivate appropriate learner mindsets, and reconfigure institutional support systems — thereby contributing to the development of scientific and technological human capital capable of navigating the evolving demands of modern universities and the knowledge-based society.